2018
DOI: 10.1136/bcr-2018-225618
|View full text |Cite
|
Sign up to set email alerts
|

Expand the differential…think beyond rheumatoid arthritis

Abstract: A 31-year-old male patient with severe, migratory arthralgias presented to our academic medical centre after being erroneously diagnosed and treated for rheumatoid arthritis for over 1 year. Multiple immunomodulatory therapies for rheumatoid arthritis were attempted with no relief of symptoms. Eventually, the pain was so bothersome that the patient became bedridden for 1 month prior to presenting to our facility. Our assessment revealed that the patient met the diagnostic criteria, known as the Yamaguchi crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…In this study, the incidence rate of AOSD was 0.625 cases per year which is lower than those calculated by other epidemiological studies [1]. The observed variation in results may be due to false diagnosis and subsequent treatment of patients for alternative medical conditions.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, the incidence rate of AOSD was 0.625 cases per year which is lower than those calculated by other epidemiological studies [1]. The observed variation in results may be due to false diagnosis and subsequent treatment of patients for alternative medical conditions.…”
Section: Discussioncontrasting
confidence: 72%
“…Furthermore, skin rashes can indicate a severe form of rheumatoid disease or even an aggressive progression of vasculitis, which warrants immediate diagnosis and intervention [ 10 ]. Such conditions require early detection and treatment because of the risks associated with disease progression and complications [ 11 ]. Immediate skin biopsy can elucidate the exact nature and severity of the condition and guide appropriate therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Adult-onset Still's disease (AOSD) is a rare systemic auto-in ammatory disorder characterized by a triad of fever, migratory arthralgia (Arthritis) and salmon-colored rash. The diagnosis is made by the Yamaguchi criteria [1]. Epidemiological studies on AOSD are limited due to its scarcity; however recent studies have shown an increased incidence and prevalence in AOSD due to increased awareness.…”
Section: Introductionmentioning
confidence: 99%